Myeloperoksidase Sebagai Prediktor Kejadian Kardiovaskular Pada Pasien Infark Miokard Akut - Starry H Rampengan; Harmani Kalim; Santoso Karo Karo; Sunarya Soerianata; Ganesja M Harimurti (Jurnal Kardiologi Indonesia, 2007)
Background. Inflammation has been linked to all stages of the develop-ment of vulnerable plaque which not only causes platelet activation but also proceeded by activation of polymorphonuclear neutrophils (PMNs). Myeloperoxidase (MPO), a hemoprotein abundantly expressed by PMNs and secreted during activation, possesses potent proinflammatory prop-erties and may contribute directly to tissue injury. Among predictors of major adverse cardiovascular events (MACE) that we have been widely used and known, such as hs-CRP and Troponin T, it still unknown whether MPO also provides prognostic information in patients with acute myocar-dial infarction (AMI). Objectives. The aim of our study is to search predictive value of MPO and to compare MPO with hs-CRP and Troponin T as a predictor of MACE in patients with AMI.Methods.Cohort-prospective study was done, conducted from April to June 2006 in the emergency department of National Cardiovascular Cen-tre - Harapan Kita, (NCVC-HK), Jakarta. MPO, hs-CRP, and troponin T serum levels were assessed in 93 patients with AMI. It recorded death, re-infarctions, angina, revascularization, and heart failure during 6 months of follow-up.Results.Patients with MPO serum level > 204,9 µg/l have increased risk of cardiovascular events (HR 6.76; 95% CI 3.37-13.56, P < 0.001). In statistical analysis, MPO (sensitivity 83.1%; specificity 82.4%) is a stronger independent predictor for subsequent cardiovascular events than Tropo-nin T (sensitivity 59.8%; specificity 71.6%) and hs-CRP (sensitivity 48.5%; specificity 46.1%).Conclusions.MPO serum levels powerfully predict an increased risk for subsequent cardiovascular events in patients with acute myocardial infarction.